Benefits of surgical treatment within 48 h of proximal femoral fracture in centenarians: a retrospective cohort study - Shitahodo, Toshiya; Murata, Shizumasa; Kitano, Yoji; Mera, Yoshimasa; Iwahashi, Hiroki; Inoue, Shingo; Kawamura, Kota; Yamada, Hiroshi (Frontiers in Surgery, 2024)
Introduction: Proximal femoral fractures in aging populations represent a significant concern, with an increasing prevalence among individuals aged ≥100 years. The existing research does not provide robust guidance for clinicians managing older patients aged ≥100 years with proximal femoral fractures. We investigated the safety and efficacy of surgical treatment in patients aged ≥100 years with proximal femoral fractures and evaluated the impact of early surgery on their outcomes. Methods: This retrospective cohort study involved 15 patients aged ≥100 years who underwent surgical treatment of proximal femoral fractures; the control group included 137 patients in their 90s. Data were collected between January 2010 and December 2017. Evaluation items included patient characteristics, surgical details, perioperative complication rates, length of hospital stay, the proportion of patients discharged to the same facility or home, rate of regaining walking ability, and 1-year survival rate. Results: The patients aged ≥100 years and those in their 90s had comparable outcomes. Thus, age alone does not dictate surgical success. Early surgery (£48 hours) was associated with trends toward improved perioperative complications, ambulatory ability, and return to original living environment. Discussion: This study underscores the potential benefits of surgical intervention for proximal femoral fractures in patients aged ≥100 years, indicating the relevance of early surgery (£48 hours). Our findings emphasized the importance of timely intervention and evidence-based decision-making for this demographic. Clinicians, policymakers, and patients could benefit from our insights to enhance fracture management strategies, along with future research endeavors to validate and expand our results in larger multicenter cohorts.